2012
DOI: 10.1097/mnm.0b013e328351d4f5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of volumetric parameters measured by F-18 FDG PET/CT in surgically resected non-small-cell lung cancer

Abstract: Volume-based parameters of F-18 FDG PET-CT may have a role in providing prognostic information in NSCLC patients who have received surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 27 publications
6
49
0
Order By: Relevance
“…MTV is a volumetric or quantitative measurement of tumor cells with high glycolitic activity, that recently has been suggested as an independent factor of prognosis in several cancers [10,[17][18][19][20]. Chung et al [10] demonstrated that the preoperative MTV more than or equal to 23.4 ml was an independent prognostic factor for disease free survival in patients with stage IB to IIA cervical cancer treated by radical surgery.…”
Section: Dicussionmentioning
confidence: 98%
“…MTV is a volumetric or quantitative measurement of tumor cells with high glycolitic activity, that recently has been suggested as an independent factor of prognosis in several cancers [10,[17][18][19][20]. Chung et al [10] demonstrated that the preoperative MTV more than or equal to 23.4 ml was an independent prognostic factor for disease free survival in patients with stage IB to IIA cervical cancer treated by radical surgery.…”
Section: Dicussionmentioning
confidence: 98%
“…For non-small cell lung cancer (NSCLC), 18 F-FDG PET/CT image quantification has been shown to provide prognostic information. PET image-derived features, including metabolically active tumor volume (MATV), mean standardized uptake value (SUV mean ), and total lesion glycolysis (TLG, defined as MATV · SUV mean ), have been shown to provide an accurate assessment of tumor burden with potentially higher prognostic value than standard maximum SUV (SUV max ), for both surgical and nonsurgical patients (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The inclusion of WB PET values in the software system, especially for the evaluation of more common and aggressive cancers (i.e. breast cancer, lung cancer, head and neck cancer, colon-rectal cancer), should be considered, in accordance with most recent evidence [14,17,24,25].…”
Section: Discussionmentioning
confidence: 91%